Openness, Economic Growth and Regional Disparities The Case of China - Jiang, Yanqing; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Substantial disparities across different Chinese regions are one of the most prominent features in China$1 (Bs development process. This book investigates the mechanisms through which openness affects regional economic growth and interregional disparities in China. Based on the latest data and employing a variety of panel data regression techniques, it provides readers with new findings that shed light on the effects of openness on China$1 (Bs regional economic growth and the evolution of the country$1 (Bs interregional disparities.s
Preface -- Introduction -- Output Growth and Productivity Growth in China -- Growth and Convergence across the Chinese Regions -- Openness and Regional Growth in China -- Openness, Human Capital, and Productivity Growth in the Chinese Regions -- Foreign Direct Investment and Regional Productivity Growth in China -- Endogenous Saving, Interregional Capital Mobility, and Convergence across China -- Inputs beyond Capital and Labor, the Neoclassical Growth Framework, and Limits to Growth in China -- Industry Mix and Interregional Disparities in China -- Openness, Structural Factors, and Economic Growth across the Regions in China -- Environmental Quality and (3z(BGreen(3y (BEconomic Growth in the Chinese Regions -- Strategic Interaction in Environmental Protection Efforts among Chinese Provincial Governments -- Strategic Competition in Public Spending on Education in Different Chinese Regions -- Trade Openness and Economic Growth in China: Models, Implications, and Some Thoughts -- A Summary and Beyond.s
Keywords: Economics; Regional planning; Endogenous growth (Economics).; Economics/Management Science; Economic Growth; Political Economy; Regional and Cultural Studies